2018
DOI: 10.1063/1.5051723
|View full text |Cite
|
Sign up to set email alerts
|

Slip statistics for a bulk metallic glass composite reflect its ductility

Abstract: Serrations in the stress-time curve for a bulk metallic glass composite with microscale crystalline precipitates were measured with exceptionally high temporal resolution and low noise. Similar measurements were made for a more brittle metallic glass that did not contain crystallites but that was also tested in uniaxial compression. Despite significant differences in the structure and stress-strain behavior, the statistics of the serrations for both materials follow a simple mean-field model that describes pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The model does not require fitting parameters or operation in the steady state, and it allows for the formation of shear bands. This model has also shown agreement with experimental results for a number of materials [e.g., [4][5][6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 77%
“…The model does not require fitting parameters or operation in the steady state, and it allows for the formation of shear bands. This model has also shown agreement with experimental results for a number of materials [e.g., [4][5][6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 77%
“…There is thus a structural component in monolithic BMGs that contributes to the scaling as shown in Figure 2(a) that so far remains fully undefined. This is much different to the case of metallic-glass matrix composites, where the statistics of stress-strain instabilities changes towards smaller event sizes [43,44] -a result that naturally emerges due to the introduction of internal micro-structural length scales where crystallites lead to shear-band deflection and arrest. [45] In fact, some first evidence has been provided that even the scaling exponent a directly scales with the volume fraction and average size of the crystalline phase.…”
Section: A Statistical Signature Of Serrated Flowmentioning
confidence: 83%
“…It has been previously observed that the introduction of crystalline dendrites into the BMG may mitigate the formation of large avalanches 34 and increase ductility 35 . Interestingly, in 34 the observed foot occurrence rate differs greatly between the monolithic metallic glass, 89%, and the composite, 19%.…”
Section: Simulationsmentioning
confidence: 99%